2003
DOI: 10.1080/02786820300947
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Versatile Aerosol Generation System for Use in a Large Wind Tunnel

Abstract: A novel aerosol generation system has been constructed for use in a large wind tunnel for two distinct research projects. One project requires a uniform aerosol concentration over the wind tunnel cross section, while the other project demands a stratified aerosol concentration distribution. The system consists of an array of venturi nozzles, which entrains particulate matter from a moving conveyor belt and disperses it into the tunnel under the force provided by a compressed air source. For the stratified rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Preliminary spot checking of the symmetry with the cylinder in place supports this assumption. This assumption is also supported by Heist et al [47], which demonstrated that the velocity proÿle was nearly constant (with a coe cient of variation of 3%) over the cross-sectional height of the empty wind tunnel. The same wind tunnel is used in this study.…”
Section: Measurements Takenmentioning
confidence: 57%
See 2 more Smart Citations
“…Preliminary spot checking of the symmetry with the cylinder in place supports this assumption. This assumption is also supported by Heist et al [47], which demonstrated that the velocity proÿle was nearly constant (with a coe cient of variation of 3%) over the cross-sectional height of the empty wind tunnel. The same wind tunnel is used in this study.…”
Section: Measurements Takenmentioning
confidence: 57%
“…For a freestream velocity of 1:0 m=s, the tunnel velocity proÿle is uniform over the cross-section with a spatial coe cient of variation of 3.0%; the turbulence intensity at this speed is 3.5%. A detailed description of this tunnel can be found in Reference [47].…”
Section: Wind Tunnelmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of this aerosol generation system can be found in Heist et al (2003). The aerosol generation system yielded a spatially uniform concentration profile across the wind tunnel test section with a CV = 6.4%.…”
Section: Experimental Datamentioning
confidence: 99%
“…With a stable, uniform concentration in the wind-tunnel, a single point measurement of freestream concentration would be sufficient to determine the upstream aerosol characteristics. Uniform particle concentration in the wind tunnel can be achieved using multiple identical particle injectors spread over the tunnel cross-section (Heist, Richmond-Bryant, Eisner & Conner 2003). Such an injection approach would, however, result in significant blockage of the cross-section, and influence the wind-tunnel flow characteristics.…”
Section: Methodsmentioning
confidence: 98%